2008
DOI: 10.1590/s1516-35982008000100016
|View full text |Cite
|
Sign up to set email alerts
|

Níveis de energia metabolizável em rações pré-iniciais para frangos de corte

Abstract: RESUMO -Um experimento foi conduzido com o objetivo de avaliar níveis de energia metabolizável em rações para frangos de corte na fase pré-inicial de crescimento. Foram alojados 280 pintos de 1 dia de idade, linhagem Avian Cobb em baterias aquecidas e distribuídas em um delineamento inteiramente casualizado com cinco tratamentos (2.850, 2.950, 3.000, 3.050, 3.150 kcal/kg de EM na ração) e quatro repetições de 14 aves por unidade experimental. Foram medidos os pesos das aves e das rações fornecidas e as sobras … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
1
3
0
1
Order By: Relevance
“…A similar result was found by Xavier et al (2008) for broilers at 7 d, when evaluating different energy levels in pre-starter feed.…”
Section: Live Weight (Kg)supporting
confidence: 86%
See 1 more Smart Citation
“…A similar result was found by Xavier et al (2008) for broilers at 7 d, when evaluating different energy levels in pre-starter feed.…”
Section: Live Weight (Kg)supporting
confidence: 86%
“…According to Xavier et al (2008), the presence of fatty acids at high levels can stimulate an increase in the secretion of digestive enzymes, promoted by hypertrophy of the secretory cells, causing an increase in the liver. Aletor et al (2003) suggest that, in high protein diets, the transport of metabolized lipids in the liver to other tissues may be increased by increased apolipoprotein synthesis, due to high availability of essential amino acids.…”
Section: Live Weight (Kg)mentioning
confidence: 99%
“…The survey results differ from those reported by Mendonça et al (2008), who found no effect of dietary energy levels (2.600, 2.750, 2.900, 3.050, 3.200 kcal / kg ME) on the weight gain of males ISA Label in periods of 1 to 21 days of age reared under semi-confined . Xavier et al (2008), analyzing the performance of chickens (Avian × Cobb) in the pre-start, no significant effect was observed with increasing levels of dietary metabolizable energy (2.850, 2.950, 3.000, 3.050 and 3.150kcal / kg).…”
Section: Resultsmentioning
confidence: 90%
“…The absolute liver weight (57.41 g) was obtained with the level of 3109 kcal/kg, and the highest relative liver weight (2.56%), with a level of 3190 kcal/kg. This effect shows that the energy levels evaluated directly influenced the metabolism of the liver and, according to Xavier et al (2008), higher amounts of metabolizable energy may increase the secretion of digestive enzymes due to hypertrophy of the secretory Table 5 -Energy level effect on body weight, weight gain, feed intake, feed:gain ratio, metabolizable energy intake of fast-growing broilers in a free-range system.…”
Section: Experiments 2 -Metabolizable Energy In Fastgrowing Broilers Imentioning
confidence: 98%